Pretreatment High MCV as Adverse Prognostic Marker in Nonanemic Patients with Head and Neck Cancer. (26th June 2020) - Borsetto, Daniele; Polesel, Jerry; Tirelli, Giancarlo; Menegaldo, Anna; Baggio, Vittorio; Gava, Alessandro; Nankivell, Paul; Pracy, Paul; Fussey, Jonathan; Boscolo‐Rizzo, Paolo
Abstract : Objective: Mean corpuscular volume (MCV) has been shown in to be a reliable prognostic marker in other cancers; however, no evidence exists on its use in head and neck squamous cell carcinoma (HNSCC). This study aimed to investigate the association between MCV, hemoglobin, platelet count and albumin concentration, and survival in stage III/IVA‐B HNSCC treated with concurrent chemoradiotherapy. Study Design: Retrospective cohort study. Methods: In this multicenter retrospective study, we analyzed MCV, platelet count, hemoglobin concentration, and albumin concentration in peripheral blood samples from 260 patients with HNSCC undergoing organ preservation treatment with curative intent at the time of diagnosis. We then analyzed survival outcomes after accounting for confounders using multivariate analysis. Results: After adjustment for potential confounders, patients with low hemoglobin had a 3.3‐fold higher risk of death (95% confidence interval [CI]: 2.26‐4.81) than those with normal hemoglobin. Patients with an elevated MCV had a 1.54‐fold higher risk of death (95% CI: 1.06‐2.24), independent of site, stage, and human papillomavirus status. Interestingly, the effect of MCV on overall and progression‐free survival was limited to those with a normal pretreatment hemoglobin. We identified no associations between pretreatment platelet count or albumin concentration and survival. Conclusion: These findings suggest that pretreatment anemia and macrocytosis are independent predictors of lower overall and progression‐free survival in HNSCC patients undergoing organ preservation treatment. Level of Evidence: III Laryngoscope, 131:E836–E843, 2021